1975
DOI: 10.1159/000264747
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Localization of Acid Phosphatase in the Injured Rabbit Lens

Abstract: The role of granular leucocytes, particularly neutrophils, during wound healing in the injured rabbit lens and the distribution of acid phosphatase were investigated using electron microscopic histochemistry. Granular leucocytes first appeared in the wound coagulum approximately after 12 h following injury. They contained granules which gave a positive reaction for acid phosphatase. At 12 and 24 h acid phosphatase localization was found to be extracellular and was most pronounced at the apical region of the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Moreover, our current preoiminary data with cytochemical localization of acid phosphatase at the ultrastructural level in lenses undergoing both development and reversal of galactose induced cataracts suggests that lysosomal enzymes probably play a role in removal of debris through its breakdown. Our previous studies on mechanically injured rabbit lens ( Unakar et at., 1975) also implicated the role of lysosomal enzymes in lens repair. We suggest that in galactose-damaged lens, hydrolytic enzymes facilitate removal of tissue debris and thus contribute toward reestablihsment of transparence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our current preoiminary data with cytochemical localization of acid phosphatase at the ultrastructural level in lenses undergoing both development and reversal of galactose induced cataracts suggests that lysosomal enzymes probably play a role in removal of debris through its breakdown. Our previous studies on mechanically injured rabbit lens ( Unakar et at., 1975) also implicated the role of lysosomal enzymes in lens repair. We suggest that in galactose-damaged lens, hydrolytic enzymes facilitate removal of tissue debris and thus contribute toward reestablihsment of transparence.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation of artifacts caused by diffusion allows one to determine the site of acid phosphatase action more pre cisely. These differences in the results obtained with the two procedures used have been discussed in detail by Essner 1973], Our previous studies with a modified Gomori method demonstrated the presence of acid phosphatase in lens tissue at the ultrastructural level [Unakar et al, 1975], In this previous investigation, the presence of acid phosphatase in mechanically injured rabbit lens was demonstrated. In our subsequent study [Unakaret al, 1977], together with the one presented in this report, we have used two separate procedures for the ultrastructural localization of acid phosphatase (Gomori and Barka-Anderson proce dures) and demonstrated the presence of this enzyme in rat lens subjected to injury through galactose feeding.…”
Section: Discussionmentioning
confidence: 77%
“…Gorthy et al [1971] and Gorthy [1978] reported the presence of acid phosphatase and lysosomes in normal and cataractous lenses of aging rats. Previous reports from our laboratory [Unakar et al, 1975] demonstrated the presence of acid phosphatase and 'This study was supported by the National Eye Institute Research Grant EY-016R0 and was part of the Cooperative Cataract Research Group (CCRG) Program. lysosomes in rabbit lens epithelium following mechanical injury. Our pre liminary studies [Unakar et ah, 1977] also revealed the presence of acid phosphatase in the intercellular spaces of lens epithelium and superficial anterior cortical fibers in rat lenses during the initial phase of galactose alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have suggested some pathologic role of lysosomal enzymes in aging and in cataracts (1,4,11,12,(15)(16)(17). Unaker et al (16,17) have reported that the ACPase activity increased during the induction of galactose cataracts and the Part of this study was presented at the thirtieth annual meeting of the Japan Society of Histochemistry and Cytochemistry held in Kyoto on October 23-25, 1989 (Tanaka, T., Sakai, M., Ihara, N. and Ogawa, K.: Localization of Acid Phosphatase Activity in the Lenses of ICR Rats).…”
mentioning
confidence: 99%